ANALISIS KESTABILAN ENDEMIK MODEL EPIDEMI CVPD (CITRUS VEIN PHLOEM DEGENERATION) PADA TANAMAN JERUK - Tesa Nur Padilah; Najmudin Fauji (Jurnal Ilmiah Matematika dan Pendidikan Matematika (JMP), 2017)
Orange fruits are important commodities in Indonesia. However, the efforts to increase production of oranges still have obstacles. One of them is because ofCVPD (Citrus Vein Phloem Degeneration) disease. The spread of CVPD disease in orange plants can be modeled by mathematical model, that is epidemic model betweenorange plants as a host plant and Diaphorina Citri as a vector. In this model, predation response follows Holling Type II response function. The model is then analyzed by checking the stability of the equilibrium point and computing basic reproduction number. This model has an endemic equilibrium point. If the basic reproduction number is more than one then an endemic equilibrium point is locally asymptotic stable or epidemic which means that it occurs in the population. The simulation result of the model are in good agreement with the model behavior analysis.